Wnt signaling in gastric cancer: current progress and future prospects - Han, Ruyue; Yang, Jing; Zhu, Yingying; Gan, Runliang (Frontiers in Oncology, 2024)
Levels of the Wnt pathway components are abnormally altered in gastric cancer cells, leading to malignant cell proliferation, invasion and metastasis, poor prognosis and chemoresistance. Therefore, it is important to understand the mechanism of Wnt signaling pathway in gastric cancer. We systematically reviewed the molecular mechanisms of the Wnt pathway in gastric cancer development; and summarize the progression and the challenges of research on molecular agents of the Wnt pathway.